Peran Guru dalam Pembentukan Karakter Siswa - Aisyah Rose Faidina; Fevni Dian Pitaloka; Yurina Eka Fadila (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
This study aims to analyze in depth the role of teachers in the formation of students’ character. The problem addressed in this research focuses on how teachers contribute to shaping students’ character amid the challenges of rapid technological development, globalization, and social change. This research employs a qualitative approach using content analysis techniques, which systematically and objectively examine written or printed information to identify relevant concepts and patterns. The results indicate that teachers have three essential roles in character formation. First, as educators, teachers integrate character values into the learning process through meaningful activities and moral guidance. Second, as instructors, teachers select appropriate learning models and strategies to develop and evaluate students’ character competencies. Third, as trainers, teachers provide exemplary behavior and cultivate positive habits through daily interactions in the school environment. These findings highlight that teachers serve not only as transmitters of knowledge but also as role models and facilitators in developing students with strong character, responsibility, and ethical awareness.